The Future of Recruitment: Analyzing the Impact of Artificial Intelligence on Evolving Hiring Processesand Strategies - shweta pandey (North American Journal of Engineering Research, 2022)
The recruitment process poses significant challenges for many organizations, often proving to be both costlyand time-consuming. The task of identifying and selecting the most suitable candidates is frequentlyhindered by subjective decision-making and inefficiencies, which can lead to suboptimal hiring outcomes.To mitigate these issues, businesses have increasingly turned to technology, incorporating internet-basedplatforms and specialized software to streamline application submissions and candidate evaluations.However, despite these technological interventions, coordinating the entire recruitment process remainslabor-intensive, requiring considerable time and financial resources. In response to these persistentchallenges, there has been a growing adoption of Artificial Intelligence (AI) in recruitment processes on aglobal scale. AI's integration into recruitment has demonstrated potential in reducing costs, minimizingdecision-making errors, and significantly improving efficiency by saving time. This paper examines thetransformative impact of AI on recruitment within the broader context of Human Resource Management(HRM). It explores the specific stages of the traditional recruitment process where AI can be effectivelyimplemented to enhance overall efficiency and effectiveness. Additionally, this paper considers the broaderimplications of AI integration in recruitment, including its potential to redefine traditional HRM practices.